The Translation of English Figures of Speech Found in the Novel Temperatures Rising into Indonesian - Pebri Pranata, I Putu (Humanis; Vol 22 No 3 (2018), 2018)
This study is entitled The Translation of English Figures of Speech Found in the novel Temperatures Rising into Indonesian. It was formulated two problems; types of figures of speech found in the novel entitled Temperatures Rising and the translation strategies implemented by translator to translate English figures of speech . It is aimed to find the types of figures speech in the novel and analyze the translation strategies implemented by the translator in the translation of the English figures of speech. The data which were used for this study were taken from an English romantic novel entitled Temperatures Rising in 1989 and its translation Hasrat Membara published by PT Gramedia Pustaka Utama in 2104 . Documentation method was used in this study by reading attentivelt and doing note-taking. Qualitative method was used to analyze the data . Besides, the result of analysis is explained descriptively. Two theories proposed by Larson were applied in this study. The first theory that mentions the type of figures of speech was used to discuss the first problem. The second theory that explains the translation strategy was used to discuss the second problem. The study showed that there were six types of English figures of speech found in the novel. Based on the second formulated problem in this study, it showed that there were only two strategies  implememted by the translator to translat e the English figures of speech.